2015
DOI: 10.5114/fn.2015.54423
|View full text |Cite
|
Sign up to set email alerts
|

Ciliary neurotrophic factor protects SH-SY5Y neuroblastoma cells against Aβ 1-42 -induced neurotoxicity via activating the JAK2/STAT3 axis

Abstract: A b s t r a c t The neurotoxicity of aggregated amyloid beta (Aβ) has been implicated as a critical cause in the pathogenesis of Alzheimer's disease (AD), which leads to neuronal cell damage by inducing oxidative stress and consequently triggering cell apoptosis. Recently, Aβ-dependent inactivation of the Janus tyrosine kinase 2/signal transducer and activator of transcription 3 (JAK2/STAT3) signaling pathway was found to play a critical role in the memory impairment related to AD. Previous research indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…METH-induced apoptosis in neuronal cells is associated with the activation of NF-κB, STAT3, and MAPK-ERK signaling [ 15 , 18 , 38 ]. We first analyzed the caspase-3 (17 kDa) and PARP (89 kDa) expression to understand the neurotoxic effects of METH on the growth of dopaminergic SH-SY5Y cells (Additional file 5 : Figure S5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…METH-induced apoptosis in neuronal cells is associated with the activation of NF-κB, STAT3, and MAPK-ERK signaling [ 15 , 18 , 38 ]. We first analyzed the caspase-3 (17 kDa) and PARP (89 kDa) expression to understand the neurotoxic effects of METH on the growth of dopaminergic SH-SY5Y cells (Additional file 5 : Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…METH is able to induce pro-inflammatory cytokines and mediators through the NF-κB and STAT3 pathways in dopaminergic and microglia cells [ 9 , 15 , 39 ]. The potential involvement of NF-κB and STAT3 was investigated because the promoters of both TNFα and IL-6 contain binding sites for NF-κB and STAT3, which are known to be involved in neurological disorders associated with increased inflammation [ 14 , 18 ]. In accordance with these findings, our results showed that AA effectively inhibits nuclear translocation of NF-κB (p65) and STAT3 in METH-stimulated dopaminergic SH-SY5Y cells, mesencephalic neurons, and BV2 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AD is associated with the production and deposition of Aβ and phosphorylated tau in APs and NFTs (1). The overloading of aggregated Aβ and phosphorylated tau will induce excessive toxicity to the neurons, which results in impairing the brains of AD patients (39,40). For neuroprotection, PGA1 has been reported to blunt N-methyl-D-aspartate receptor (NMDAR)-mediated neuronal apoptosis and inhibits enhancement of the intracellular calcium concentration, TXA 2 production, and platelet activation in rodent models of stroke (41).…”
Section: Discussionmentioning
confidence: 99%
“…Tong et al have demonstrated that NgR silencing inhibits C6 cell proliferation and promotes cell apoptosis ( 21 ). Wang et al have reported that CNTF protects neuroblastoma SH-SY5Y cells from cytotoxicity and apoptosis induced by amyloid beta peptide (Aβ 1–42 ) ( 22 ). However, the effect of NgR knockdown or CNTF treatment and their synergistic effect on RGC-5 cells needed to be clarified.…”
Section: Discussionmentioning
confidence: 99%